Blockade of the 4-1BB (CD137)/4-1BBL and/or CD28/CD80/CD86 costimulatory pathways promotes corneal allograft survival in mice - Asai, Tatsuhiko (Blackwell Science Inc, 2007)
To explore the roles of 4-1BB (CD137) and CD28 in corneal transplantation, we examined the effect of 4-1BB/4-1BB ligand (4-1BBL) and/or CD28/CD80/CD86 blockade on corneal allograft survival in mice. Allogeneic corneal transplantation was performed between two strains of wild-type (WT) mice, BALB/c and C57BL/6 (B6), and between BALB/c and B6 WT donors and various gene knockout (KO) recipients. Some of the WT graft recipients were treated intraperitoneally with agonistic anti-4-1BB or blocking anti-4-1BBL monoclonal antibody (mAb) on days 0, 2, 4 and 6 after transplantation. Transplanted eyes were observed over a 13-week period. Allogeneic grafts in control WT B6 and BALB/c mice treated with rat immunoglobulin G showed median survival times (MST) of 12 and 14 days, respectively. Allogeneic grafts in B6 WT recipients treated with anti-4-1BB mAb showed accelerated rejection, with an MST of 8 days. In contrast, allogeneic grafts in BALB/c 4-1BB/CD28 KO and B6 CD80/CD86 KO recipients had significantly prolonged graft survival times (MST, 52·5 days and 36 days, respectively). Treatment of WT recipients with anti-4-1BB mAb resulted in enhanced cellular proliferation in the mixed lymphocyte reaction and increased the numbers of CD4(+) CD8(+) T cells, and macrophages in the grafts, which correlated with decreased graft survival time, whereas transplant recipients with costimulatory receptor deletion showed longer graft survival times. These results suggest that the absence of receptors for the 4-1BB/4-1BBL and/or CD28/CD80/CD86 costimulatory pathways promotes corneal allograft survival, whereas triggering 4-1BB with an agonistic mAb enhances the rejection of corneal allografts.